Selection of solutions in multi-objective optimization: Decision making and robustness - Gaspar-Cunha, A. (2015)
A multidisciplinary design an optimization framework based on the use of multi-objective evolutionary algorithms, together with decision making and robustness strategies, was used to optimize the polymer extrusion process. This methodology was applied with the aim to select the best solutions from the Pareto set in a multi-objective environment. The application to a complex polymer extrusion case study demonstrated the validity and usefulness of the approach.